1996
DOI: 10.1002/j.1460-2075.1996.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-dependent cognate amino acid recognition by an aminoacyl-tRNA synthetase.

Abstract: An investigation of the role of tRNA in the catalysis of aminoacylation of Escherichia coli glutaminyl‐tRNA synthetase (GlnRS) has revealed that the accuracy of specific interactions between GlnRS and tRNAGln determines amino acid affinity. Mutations in GlnRS at D235, which makes contacts with nucleotides in the acceptor stem of tRNAGln, and at R260 in the enzyme's active site were found to be independent during tRNA binding but interactive for aminoacylation. Characterization of mutants of GlnRS at position 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 59 publications
(30 reference statements)
6
33
0
Order By: Relevance
“…As an initial step, we extended this analysis to the determination of individual k cat and K m parameters of the steady-state reaction with respect to glutamine and tRNA Gln (Table 1). These parameters are nearly identical to those determined with the conventional assay, further verifying that this experimental approach is suitable for quantitative kinetic studies (14,23,24).…”
Section: Assay For Steady-state and Single-turnover Aminoacylation Kisupporting
confidence: 72%
See 1 more Smart Citation
“…As an initial step, we extended this analysis to the determination of individual k cat and K m parameters of the steady-state reaction with respect to glutamine and tRNA Gln (Table 1). These parameters are nearly identical to those determined with the conventional assay, further verifying that this experimental approach is suitable for quantitative kinetic studies (14,23,24).…”
Section: Assay For Steady-state and Single-turnover Aminoacylation Kisupporting
confidence: 72%
“…Further transient kinetics experiments together with simulations and global fitting will be required to derive K d in these circumstances (25,27). Determination of k off for tRNA binding to the unliganded enzyme by fluorescence showed that this parameter is comparable in magnitude to the k chem determined here, consistent with the notion that the tRNA is not in rapid equilibrium (24).…”
Section: Assay For Steady-state and Single-turnover Aminoacylation Kisupporting
confidence: 64%
“…A similar discrepancy between k on and k cat /K m was also observed for the hydrolysis reaction catalyzed by the RNA component of RNase P (26), and may indicate the existence of a distinct, nonequilibrating enzyme species formed during the process of product dissociation and subsequent substrate rebinding. Determination of the tRNA off-rate in a binary complex with GlnRS by fluorescence previously yielded k off(tRNA) ϭ 7 s Ϫ1 , suggesting that the affinity for tRNA in the context of a catalytically competent quaternary complex is somewhat weakened relative to a binary complex (27). This is consistent with the need for rapid turnover in the steady state.…”
Section: ϫ1 Smentioning
confidence: 65%
“…Although we suggest that this conformation change is important in achieving discrimination, it is likely that other factors are operative as well. It appears that the discrimination process between cognate and noncognate tRNAs is a dynamic one involving conformational changes, substrate binding linkages (Bhattacharyya & Roy, 1993;Hong et al, 1996) and optimization of several functions (Sherman & Soll, 1996).…”
Section: Discussionmentioning
confidence: 99%